A multidisciplinary approach to tackling invasive species: barcoding, morphology, and metataxonomy of the leafhopper Arboridia adanae - Piccinno, Riccardo; Tatti, Alessia; Avosani, Sabina; Galla, Giulio; Lazazzara, Valentina; Pedrazzoli, Federico; Rota-Stabelli, Omar (Nature Portfolio, 2024)
The leafhopper genus Arboridia includes several species that feed on Vitis vinifera and cause leaf chlorosis. We report the first alien Arboridia infestation in Italy in 2021 in an Apulian vineyard. To confirm the taxonomic status of the species responsible for crop damage, and reconstruct its demographic history, we barcoded individuals from Apulia together with Arboridia spp. from Crete (Greece), A. adanae from Central Turkey and other specimens of the presumed sister species, A. dalmatina from Dalmatia (Croatia). Molecular phylogenies and barcoding gap analysis identified clades not associated with sampling locations. This result is incongruent with classical specimen assignment and is further supported by morphological analyses, which did not reveal significant differences among the populations. Therefore, we propose A. dalmatina as a junior synonym of A. adanae, which would become the only grapevine-related Arboridia species in the eastern Mediterranean. To further characterise A. adanae evolution, we performed a molecular clock analysis that suggested a radiation during the Pleistocene glaciations. Finally, to assess whether the Apulian individuals carried microorganisms of agricultural relevance, we sequenced their bacterial microbiota using 16S rRNA amplicon sequencing identifying three phytopathogens not generally associated with Arboridia activities as well as Wolbachia in one Apulian haplogroup. We discuss the agricultural implications of this infestation.
Keywords: Phylogenetic Analysis; Sequence Alignment; Cicadellidae; Wolbachia; Hymenoptera; Homoptera; Evolution; Mymaridae; Climate; Biology